Availability and Patterns of Intravesical BCG Instillations - Poletajew, Slawomir; Majek, Aleksandra; Magusiak, Piotr; Sledzikowska, Katarzyna; Dybowski, Bartosz; Radziszewski, Piotr (Urology Journal, 2017)
Purpose: Intravesical BCG instillations improve recurrence free survival in patients with non-muscle-invasive bladder cancer (NMIBC). Methods: This is a national survey study, covering 223 urological centres, aimed at reliable identification of BCG availability and implemented treatment patterns. Results: Response rate was 93.7%. BCG was used in 56.5% of urological departments. Another 22.7% referred patients to other hospitals for instillations, while 20.8% did not recommend BCG at all. The most common indications for BCG instillations were as follows: T1 tumours (88.5%), carcinoma in situ (83.6%) and high grade tumours (73.8%). Maintenance therapy was routinely abandoned in 16.4% of centres or was scheduled for <1 year, 1 year, 3 years and 1-3 years in 6.6%, 19.7%, 21.3% and 31.2% of centres, respectively. Continuation of BCG despite treatment failure in carcinoma in situ cases was considered in 21.3% of departments. Conclusion: Our findings indicate that BCG is underused, while patterns of maintenance and follow-up are suboptimal.